Studi Tanaman Penghijauan Glodokan Tiang (Polythea longifolia), Kasia Emas (Cassia surattensis), Kelapa (Cocos nucifera) sebagai Penyerap Emisi Gas Karbondioksida di Jalan PB. Sudirman Denpasar - AGUSTINA REZA PUTRI; KOMANG ARTHAWA LILA; I NYOMAN GEDE ASTAWA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT The Study of Glodokan Tiang (Polythea longifolia), Kasia Emas (Cassia surattensis), Coconut (Cocos nucifera) Plant as Absorbent of Carbon Dioxide Emission at PB. Sudirman Street Denpasar The research was conducted at the green belt at PB. Sudirman Street Denpasar City on May-November 2011. This study aim to find out the ability of glodokan tiang (Polythea longifolia), kasia emas (Cassia surattensis), and coconut (Cocos nucifera) plant as absorbent of carbon dioxide emission at PB. Sudirman Street Denpasar. The research method have been used in this research were exploration method, that is determine the mass of carbon dioxide from mass of carbohydrate formed, whereas to determine the mass of carbon dioxide were conducted an analysis by using spectrometry. The results of study shows that the highest mass of carbon dioxide have been obtained successively: coconut at 48,0344 mg/50 ml, then glodokan tiang plant (32,8890 mg/50 ml), and kasia emas (25,0916 mg/50 ml). Keyword: Study of Plant, Absorbent, Carbon Dioxide Emissions